DAMPAK PEMBERIAN HAK OPSI SAHAM KARYAWAN SEBAGAI BENTUK INSENTIF TERHADAP KINERJA KEUANGAN PERUSAHAAN PUBLIK DI BURSA EFEK INDONESIA (BEI) - Aditya Priansyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purpose of this research is to assess the effect of employee stock option program implemented in corporation on financial performance. Financial ratio of return on asset (ROA) and return on equity (ROE) are chosen as proxies to measure financial performance. This research also uses financial leverage and company size as the controlling variable. The samples of this research are companies listed in the Indonesia Stock Exchange (IDX) that had announced and implemented employee stock option program from 2000 to 2013. Using purposive sampling method as the sampling method, the researcher has obtained 32 companies that meet the criteria and has used them as samples in this research. This research uses multiple regression analysis as the analysis method. The result of this research shows that employee stock option does not have any effect on ROA and ROE. From the results of this research, there is no evidence that the implementation of employee stock option program can give positive impact on financial performance.Keyword: Employee Stock Option, Employee Stock Ownership Program, Agency Theory, Incentive, Financial Performance, Return on Asset (ROA), Return on Equity (ROE)